Transition of the initial mass function in the metal-poor environments. Issue 3 (7th September 2021) - Chon, Sunmyon; Omukai, Kazuyuki; Schneider, Raffaella
ABSTRACT: We study star cluster formation in a low-metallicity environment using three-dimensional hydrodynamic simulations. Starting from a turbulent cloud core, we follow the formation and growth of protostellar systems with different metallicities ranging from 10 −6 to 0.1 Z⊙ . The cooling induced by dust grains promotes fragmentation at small scales and the formation of low-mass stars with M * ∼ 0.01–0.1 M⊙ . While the number of low-mass stars increases with metallicity, when Z /Z⊙ ≳ 10 −5, the stellar mass distribution is still top-heavy for Z /Z⊙ ≲ 10 −2 compared to the Chabrier initial mass function (IMF). In these cases, star formation begins after the turbulent motion decays and a single massive cloud core monolithically collapses to form a central massive stellar system. The circumstellar disc preferentially feeds the mass to the central massive stars, making the mass distribution top-heavy. When Z /Z⊙ = 0.1, collisions of the turbulent flows promote the onset of the star formation and a highly filamentary structure develops owing to efficient fine-structure line cooling. In this case, the mass supply to the massive stars is limited by the local gas reservoir and the mass is shared among the stars, leading to a Chabrier-like IMF. We conclude that cooling at the scales of the turbulent motion promotes the development of the filamentary structure and works as an important factor leading to the present-day IMF.